Identification of risk in project management – practitioners and experts - Soroka-Potrzebna, Hanna (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
Each project is assumed to carry some risk. Risk can be limited or used, but it is necessary to identify it. The literature on the subject describes many risk identification methods that differ in the specificity of use. The article aims to compare the risk identification process used by project teams with the recommendations of CERT IPMA Polska assessors. For this purpose, an analysis of surveys and interviews was used. The results of the research allowed to show how the risk is perceived, to which risks particular attention is paid, whether the identification of risk before the start of the project is important and what methods are used and recommended for this purpose.